Comparison of lipases for in vitro models of gastric digestion: lipolysis using two infant formulas as model substrates. Issue 9 (26th August 2016) - Sassene, P. J.; Fanø, M.; Mu, H.; Rades, T.; Aquistapace, S.; Schmitt, B.; Cruz-Hernandez, C.; Wooster, T. J.; Müllertz, A.
Abstract : The aim of this study was to find a surrogate for Human Gastric Lipase (HGL), since the development of gastrointestinal lipolysis models are hampered by the lack of a lipase with similar digestive properties as HGL. Abstract : The aim of this study was to find a lipase suitable as a surrogate for Human Gastric Lipase (HGL), since the development of predictive gastrointestinal lipolysis models are hampered by the lack of a lipase with similar digestive properties as HGL. Three potential surrogates for HGL; Rhizopus Oryzae Lipase (ROL), Rabbit Gastric Lipase (RGL) and recombinant HGL (rHGL), were used to catalyze the in vitro digestion of two infant formulas (a medium-chain triacylglyceride enriched formula (MC-IF) and a predominantly long-chain triacylglyceride formula (LC-IF)). Digesta were withdrawn after 0, 5, 15, 30, 60 min of gastric digestion and after 90 or 180 min of intestinal digestion with or without the presence of pancreatic enzymes, respectively. The digesta were analyzed by scanning electron microscopy and gas chromatography to quantify the release of fatty acids (FAs). Digestions of both formulas, catalyzed by ROL, showed that the extent of gastric digestion was higher than expected from previously published in vivo data. ROL was furthermore insensitive to FA chain length and all FAs were released at the same pace. RGL and rHGL favoured the release of MC-FAs in both formulas, but rHGL did also release some LC-FAs during digestion of MC-IF, whereas RGL only released MC-FAs. Digestion of a MC-IF by HGL in vivo showed that MC-FAs are preferentially released, but some LC-FAs are also released. Thus of the tested lipase rHGL replicated the digestive properties of HGL the best and is a suitable surrogate for HGL for use in in vitro gastrointestinal lipolysis models.